Odgoj za vrijednosti u okvirima kurikula predmeta društveno-humanističkoga područja - Brković, Vjera; Bušljeta Kardum, Rona; Mališa, Snježana (2021)
Područje odgoja za vrijednosti interdisciplinarno je s obzirom na to da se tom temom bave znanosti poput filozofije, pedagogije, psihologije, antropologije, religijskih znanosti, kao i međupredmetne kurikulne teme. U okviru odgojno–obrazovnih znanosti nameće se pitanje za koje vrijednosti odgajati mlade. Cilj je ovoga rada sažeto prikazati razvoj odgojno–obrazovnih vrijednosti kroz povijest, definirati pojam odgojno–obrazovnih vrijednosti te analizom kurikula nastavnih predmeta društveno–humanističkoga područja odgovoriti na pitanje koje se vrijednosti razvijaju kroz odgoj i obrazovanje.
In this paper, we have explored the development of values education throughout history and offered a definition of the concept of values in contemporary literature. An analysis of the Social Sciences and Humanities curricula is used to present a systematic overview of values, the development of which is encouraged in the Croatian education system. We have found no decisive conclusions in theories of education as to whether values should be fostered in each subject, however, the National Curriculum Framework, as a basic education document, suggests that certain values should be promoted in the teaching and learning processes, and that students should be encouraged to adopt them. The National Curriculum Framework defines eight educational values that should be incorporated into the outcomes of all school subjects. These are: knowledge, solidarity, identity, responsibility, integrity, respect, health and enterprise. The results of our research showed that knowledge is the primary value found in all subject curricula. Other values are also represented but not to the same extent. Based on the results obtained, we can conclude that the teaching and learning processes are focused on acquiring factual knowledge but also provide an opportunity for values education.
Bibliografske bilješke uz tekst ; bibliografija: str. 198-200.
Sažetak ; Summary.
Keywords: Odgoj i obrazovanje -- Društveno-humanističko područje -- Kurikulum -- Vrijednosti